2014
DOI: 10.1021/jf500505n
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Analysis of Antimicrobial Mechanisms of ε-Poly-l-lysine on Saccharomyces cerevisiae

Abstract: ε-Poly-L-lysine (ε-PL), a naturally occurring amino acid homopolymer, has been widely used as a food preservative. However, its antimicrobial mechanism has not been fully understood. This study investigated the antimicrobial mode of action of ε-PL on a yeast, Saccharomyces cerevisiae. When treated with ε-PL at the concentration of 500 μg/mL, cell mortality was close to 100% and the phospholipid bilayer curvature, pores, and micelles on the surface of S. cerevisiae were clearly observed by scanning electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 37 publications
5
31
0
Order By: Relevance
“…As the concentrations were increased, more obvious changes appeared on the cell surfaces. These findings were consistent with that of Bo et al, 26 who studied the effects of -PL on Saccharomyces cerevisiae cells. Their results indicated that -PL could cause many voids to appear on the surfaces of Saccharomyces cerevisiae cells.…”
Section: Effect Of -Pl On the Morphology Of B Cereussupporting
confidence: 93%
“…As the concentrations were increased, more obvious changes appeared on the cell surfaces. These findings were consistent with that of Bo et al, 26 who studied the effects of -PL on Saccharomyces cerevisiae cells. Their results indicated that -PL could cause many voids to appear on the surfaces of Saccharomyces cerevisiae cells.…”
Section: Effect Of -Pl On the Morphology Of B Cereussupporting
confidence: 93%
“…10). Because ε-PL interacts more readily with negatively charged headgroups, it has a relatively low toxicity against mammalian cells (8) and yeast cells (3,45), and differences in susceptibility among microorganisms could be caused by differences in membrane composition. For example, the membrane of L. innocua contains lysine-derivatized phosphatidylglycerol and lysylcardiolipin (19,46,47).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the activity of amphotericin B against C. albicans can be attributed to changes in metabolite production (Cao et al, 2013). Another study found that the microbiostatic effect of ε-Poly-L-lysine on Saccharomyces cerevisiae is achieved by breaking the balance of intracellular metabolites due to disruptions in cell membrane function (Bo et al, 2014). Finally, a metabolomics approach was used to demonstrate that cinnamaldehyde changes the metabolism of E. coli by interacting with different biochemical targets (Mousavi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%